Genetic Manipulation of M13 Bacteriophage for Enhancing the Efficiency of Virus‐Inoculated Perovskite Solar Cells with a Certified Efficiency of 22.3%. Issue 38 (2nd September 2021) - Han, Jiye; Kim, Kyusun; Nam, Jeong‐Seok; Hong, Sung Jun; Choi, Eun Jung; Kim, Dawoon; Chung, In; Lin, Hao‐Sheng; Kim, Tae‐Dong; Strano, Michael S.; Han, Byungchan; Oh, Jin‐Woo; et al.
Abstract: Perovskite solar cells (PSCs) are considered to be one of the most promising solar energy harvesters owing to their high power conversion efficiency (PCE). To increase their PCE even further, additives are used; however, some of these additives pose certain disadvantages, which limit their applications to PSCs. Therefore, in this study, the nature‐inspired ecofriendly M13 bacteriophage is genetically engineered to maximize its performance as a perovskite crystal growth template and as a passivator for PSCs. The genetic manipulation of the M13 bacteriophage enhances the Lewis coordination between the perovskite materials and single‐stranded virus by amplifying a designated amino acid group. Among the 20 types of amino acids, lysine (Lys or K), arginine (Arg or R), and methionine (Aug or M) exhibit the strongest interaction with the perovskite materials. Results suggest that the K‐amplified genetically engineered M13 bacteriophage is the most effective. The K‐type M13 virus‐inoculated PSCs yield a PCE of 23.6% in the laboratory. This device, when taken to a national laboratory for verification, exhibits a certified forward and reverse bias‐combined efficiency (22.3%), which, to the best of the authors' knowledge, is one of the highest efficiencies reported among the biomaterial‐based PSCs. Abstract : Genetic modification of M13 bacteriophages amplifies amino acid K, which functions as a perovskite growth template and a stronger passivator than the wild‐type virus in PSCs. The modified virus‐added PSCs exhibit a higher PCE (23.6%) than wild‐type M13 virus‐added devices (22.8%). The observed enhancement is attributed to slightly larger perovskite grains, stronger grain boundary passivation, and improved hole conductivity.